Size-fraction-specific stable isotope variations in early Eocene bulk sediment carbon isotope records of ODP Site 198-1209 - Bhattacharya, Joyeeta; Yeung, Laurence Y; Cong, Lin; Dickens, Gerald Roy; Sun, Tao (PANGAEA, 2021)
Here we present changes in abundances and δ13C and δ18O composition of five size fractions of bulk sediments from ODP Site 1209 in Shatsky Rise, north-central Pacific, deposited BETWEEN 58-50 Ma. The dataset includes four tables. The bulk sediments were rinsed and segregated into five size fractions: <25 μm, 25-63 μm, 63-125 μm, 125-250 μm and >250 μm. The difference in mass of sediments before and after size-fraction separation is reported in the first sheet. The second sheet documents temporal changes in relative weights of the various size fractions: namely fine fraction (FF), intermediate fraction (IF), coarse fraction (CF) and the three sub-fractions of CF. The δ13C and δ18O composition of bulk sediments and size fractions are reported in the third and fourth sheets, respectively.
Keywords: Bulk Carbonates; Carbon Isotope Excursions; chemostratigraphy; Coarse fraction; Hyperthermals; PETM